Protocol on a systematic review of nomenclature and outcomes in children with complex critical illness in Paediatric Critical Care: The basis for consensus definition - Sofia Cuevas-Asturias; Claire Rafferty; Hannah Mitchell; William Tremlett; Padmanabhan Ramnarayan; Natalie Pattison (PLoS ONE, 2025)
Introduction Paediatric Critical Care (PCC) supports the recovery of children with severe illness. In the UK, there are 30 PCC units with a total of approximately 400 beds. There is constant demand for these beds with a mean five-day length of stay and admissions increasing at a greater rate than age-specific population growth. Prolonged stay patients account for approximately half of all PCC patient bed days. Children with complex critical illness (CCI) need input from multiple different teams alongside support for their family. CCI often become prolonged PCC-stay patients too. Internationally, there is variation in the definition of CCI, this creates service variation and tensions around what resources can be provided including discharge planning, provision, and support. Objective: The face of Paediatric Critical Care, in the UK and internationally has changed over the last ten years with a growing cohort of complex critically ill patients. This systematic review aims to look at current nomenclature, criteria, and outcome measures of priority in this undefined patient population. Methods and materials Inclusion criteria: All types of studies examining children with complex critical illness (age <18 years) admitted to any paediatric critical care. The review is registered on Prospero. Medline, Embase, Maternity and Infant care, The Cochrane Library, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), and the Trip database will be searched from 2014 to May 2024. The search was limited to ten years as children with complex critical illness are a relatively new concept within PCC. Therefore, the timeline was limited to increase the accuracy and applicability of the review. Search limits included all languages, excluded the setting of neonatal intensive care, and age>18 years old. The final search strategy was developed in Medline and peer-reviewed by a health research librarian not involved in the study. This was translated to other databases as appropriate. Four independent reviewers will screen citations for eligible studies and perform data extraction. Discussion A systematic review methodology has been used to develop a broad understanding of the literature which will be used to develop further work in this area. Using a rigorous and stepwise approach, the whole spectrum of scientific publications on children with complex critical illness in paediatric intensive care will be reviewed, ensuring this study is as comprehensive as possible. This includes quantitative, qualitative, theoretical, and grey literature. A limitation of this systematic review is the use of many terms to describe children with complex critical illness in the literature resulting in a high number of publications on this topic.